Implementasi Hadis Sabar dalam Menuntut Ilmu dan Implikasinya Terhadap Mahasiswa Rantau - Septi Nuraini, Wahyu Griza; Murtini, Nurul Budi (Universitas Islam Negeri Alauddin, 2024)
Demanding knowledge is an obligation in Islam for all human beings, both men and women. Patience in demanding knowledge is very necessary for knowledge claimants, because the path of demanding knowledge is very havy and there are many obstacles, especially knowledge claimants who are migrating from their hometown. STDI Imam Syafi’i Jember is a private university located on Jalan MH. Thamrin Gg. Kepondang No. 05, Gladak Pakem, Keranjingan, Sumbersari District, Jember Regency, East Java. The purpose of this study is to analyze and find the hadith of patience and hadith of studying, the motivating factors for female students to migrate to study and the problems they are facing in the overseas land, and the implications after practicing the Hadith of patience in studying. The approach used in this research is a qualitative approach. The result of this study indicate that the interpretation of the hadith of patience is that anyone who tries to always be grateful and remain patient with the circumstances he is experiencing, then Allah will give something better and more spacious than his patience. Meanwhile, the interpretation of the Hadith of studying is that Allah will make it easy for His servants to get guidance and taufiq to heaven. The impact of practicing the hadith of patience in studying is to become calmer, to become more patient, and expand the heart. Keywords: Implementation, Hadith, Patience, Demanding Knowledge, Implications.